2010
DOI: 10.5897/ajb10.933
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the antioxidant effect of Kigelia africana fruit extract (Bignoniacieae) in male Sprague-Dawley rats

O O2,
et al.

Abstract: Testicular germ cells as well as epididymal maturing spermatozoa are endowed with enzymatic and non-enzymatic scavenger systems to protect lipid peroxidation damage. A number of pathologies and systemic challenges can lead to an antioxidant/pro-oxidant disequilibrium. With increasing interest in herbal therapies for management of some fertility-related and inflammatory conditions, we investigated the antioxidant effect of Kigelia africana fruit extract (KAFE) on normal rats. KAFE showed a non-dose dependent el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…It was determined that the most efficient method for utilizing microwave radiation as a pretreatment process was at lower power levels in combination with dilute NaOH. Ragitapai was chosen based on its ability toproduce glucose and ethanol yields from starch directly as presented previous by other researches, but with low yields 47 . The present study had also highlighted the importance of well controlled microwave assisted enzymatic reaction to enhance the overall reaction rate of the process.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined that the most efficient method for utilizing microwave radiation as a pretreatment process was at lower power levels in combination with dilute NaOH. Ragitapai was chosen based on its ability toproduce glucose and ethanol yields from starch directly as presented previous by other researches, but with low yields 47 . The present study had also highlighted the importance of well controlled microwave assisted enzymatic reaction to enhance the overall reaction rate of the process.…”
Section: Resultsmentioning
confidence: 99%
“…5-6) were observed indicating impaired lipid metabolism in the testis as suggested by earlier reports in both administrations 37 . It was reported that the lipid composition of the sperm membrane exert a significant effect upon the functional quality of spermatozoa [38][39] , Spermatozoa are rich in polyunsaturated fatty acids, which are more liable for lipid peroxidation by reactive oxygen species (ROS) 40 . Hence, the administrations of OS and UA bring the alterations in lipid composition which leads to changes in functional quality of spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced renal injury contributes up to 25% of all cases of acute renal failure 10 . Recent interest has focused on complementary and alternative medicines for the treatment of various diseases 11 and our previous studies 8,12 support the increasing utilization of plant-based adjuvants for disease management. Many of the biological functions of flavonoids and phenolic compounds have been attributed to their free radical scavenging and anti-oxidant activities 12,13 .…”
Section: African Health Sciences Vol 17 Issue 1 March 2017 164mentioning
confidence: 99%
“…Recent interest has focused on complementary and alternative medicines for the treatment of various diseases 11 and our previous studies 8,12 support the increasing utilization of plant-based adjuvants for disease management. Many of the biological functions of flavonoids and phenolic compounds have been attributed to their free radical scavenging and anti-oxidant activities 12,13 . Studies have also shown the ability of kolaviron (kv) to protect against various noxious compounds like phalloidin, amanita, 2-acetylaminofluorene, carbon tetrachloride, paracetamol, aflatoxin and dimethyl nitrosamine in the liver of rodents 14 .…”
Section: African Health Sciences Vol 17 Issue 1 March 2017 164mentioning
confidence: 99%